2017
DOI: 10.1007/s13205-017-0841-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant production of Aspergillus Flavus uricase and investigation of its thermal stability in the presence of raffinose and lactose

Abstract: Aspergillus flavus uricase (Rasburicase) with a molecular mass of 135 kDa is currently used for the treatment of gout and hyperuricemia occurring in tumor lysis syndrome. To characterize the effects of raffinose and lactose osmolytes on the uricase structure, its coding sequence was cloned, expressed in E. coli BL21, and purified by Ni-NTA agarose affinity chromatography. Thermal inactivation studies at 40 °C showed that nearly 15% of UOX activity was preserved, while the presence of raffinose and lactose redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…The retained activity of uricase from B. subtilis is ~ 50% after incubation at 37 °C for 12 h (Pfrimer et al 2010). Only 15% of uricase activity from A. flavus is preserved after 10-min incubation at 40 °C (Imani and Shahmohamadnejad 2017). In the present study, the specific activity of KmUOX was 50.54 U mg −1 , which is rather high relative to the reported uricases.…”
Section: The Optimal Temperature and Temperature Stability Of The Tagcontrasting
confidence: 50%
“…The retained activity of uricase from B. subtilis is ~ 50% after incubation at 37 °C for 12 h (Pfrimer et al 2010). Only 15% of uricase activity from A. flavus is preserved after 10-min incubation at 40 °C (Imani and Shahmohamadnejad 2017). In the present study, the specific activity of KmUOX was 50.54 U mg −1 , which is rather high relative to the reported uricases.…”
Section: The Optimal Temperature and Temperature Stability Of The Tagcontrasting
confidence: 50%
“…Some urate oxidases with high specific activity are not so thermostable. The urate oxidase from A. flavus retains only 30% activity after incubation at 40 °C for 1 h; its specific activity is 27 U mg −1 [ 14 , 41 ]. The urate oxidase from C. utilis retains only 40% activity after incubation at 37 °C for 24 h; its specific activity is 38.4 U mg −1 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that at elevated temperatures (i.e., around and above 40 • C), the tetrameric Uox enzyme tends to disassociate into the inactive monomeric subunits [12]. For example, it was shown that at 35 • C, the Uox could lose its activity to below 20% of its original activity level, and also with any further increase in temperature, the Uox activity may decline further [73]. In addition, this inactivation has also been shown to happen in a concentration-dependent manner.…”
Section: Thermal Inactivation and Thermal Stability Studiesmentioning
confidence: 99%